Exercício resistido na composição corporal, perfil lipídico, glicemia e aptidão física de mulheres obesas - Takehara, Júlio César (Universidade Federal de São Carlos, 2008)
Currently there is a lot of knowledge about the effects of non resistant cyclic exercises such as the racing, the swimming, and the cycling. However the resistant exercises even though more practiced (the working out) still need more scientific explanation, mainly concerning to the obese population. The goal of this research is to determine the effect of the resisted exercise practice in different intensities on the corporeal composition and the physical capability in obese women. Thirty three volunteers of the female gender participated from this research, thirteen of them working out in low intensity (Lower RER group L), fourteen working out in moderate intensity (threshold anaerobic group M) and six that were part of the control group. All the volunteers went through a corporeal composition evaluation, maximum consumption of oxygen, maximum muscular strength, yet increasing test in resistant exercises were taken besides pre and pos working out practice clinic exams. Media descriptive statistics was used and pattern deviation to demonstrate the data and it was opted by the curtose and asymmetry analysis, after the one way Anova variance analysis was performed at every variance and to those which were considered significant as post hoc the Tukey test. It was established for the rejection the hypothesis of nullity (H0) p < 0, 05. There can be observed decrease in the following variances: corporeal weight 7% to group L and 10,5% to group M; BMI of 7,8% to group L and 10,5% to group M; %F 11,8% to group L and 24,1% to group M; FM 19% to group L and 32,3% to group M. Yet, increase was gotten to the following variances: FFM 5,6% to group M; VO2 max. of 51,8% to group L and 63,4% to group M. Regarding to the muscular strength to the superior members there was an improvement of 45,6% to group L and of 68,8% to group M, then to the inferior members there was an improvement of muscular strength of 49,9% to group L and of 68,9% to group M. According to these results it follows that even with the improvements of the corporeal composition, physical capability level and muscular strength to both working out practice intensities, it is important to remind that initiating a physical working out practice mainly to sedentary people it is necessary a postural adaptation to this kind of working out practice, so that lesions won t occur. Thus the lowest intensity is easier to correct the posture in the various working out equipments.
Keywords: Exercício resistido; Fisiologia do exercício físico; Obesidade; Análise de força muscular; Resistant exercise; Strength practice; Working out and obesity; CIENCIAS BIOLOGICAS::FISIOLOGIA